Testing the arbitrage pricing theory on the Tehran stock exchange - Sabetfar, Pooyar (2011)
The equilibrium-pricing model using Arbitrage Pricing Theory (APT) has become one of the central models of modern financial theory. However, the APT is too general in determining the factors which influences expected returns. Many empirical studies on the APT have already been conducted in free enterprise systems but, no attention has been given in full Sharia compliant close economy. Since there was no previous research on the study of APT in full Sharia compliant sanction economy, an empirical support for the APT by employing macroeconomic variables in Tehran Stock Exchange (TSE) which works in full Sharia compliant sanction economy was examined as the main objective of the research. However, this study identifies the macroeconomic variables that may have significant high impact on the stock market returns in the arbitrage pricing relationship. Also, this research aims to see whether economical and financial sanctions adversely affect stock market returns. This study undertakes to identify the number of common factors, priced factors and the macroeconomic variables that significantly affect on TSE by employing factor analysis with principal component method from 1991-2008. Canonical Correlation Analysis (CCA) is also used to see effect of macroeconomic variables on stock returns in TSE. In this study, all the procedure is done by using individual security and grouping according to different size of portfolios separately. The evidence points to at least one factor to three factors that explain the cross-section of expected returns in TSE from 1991-2008. Financial and economical sanctions are affecting stock market returns and the negative sign of coefficients show the opposite reaction of investors to the announcement of sanctions in TSE. The principal component analysis results suggest that there are four groups of macroeconomic variables in the test period that affect stock returns. According to CCA results in the samples, the sources of systematic risk in the period are export of the crude oil and interest rate proxy in TSE. The results show the validly but, weak applicability of APT to estimate expected returns of the securities in full Sharia closed economy. Nevertheless, the macroeconomic variables that influence stock market returns change over time in Iranian context. This probably is a typical aspect of sanctioned market. The results also recommend the dissimilar strategies are needed to invest successfully in Iran because it is more sensitive to sanctions and different macroeconomic variables.